Peradaban Islam; Epistemologi Peradaban dan Perubahan Dunia - khofifah Al Adawiyah; Iis , Neng; Fathiyah, Najma Syaidatul; Natasya TMB, Leksa; Syamsul , E Mulya (Al-Akhbar: Jurnal Ilmiah Keislaman, 2024)
This article aims to reveal the meaning of civilization in the context of epistemology, while the focus of the problem raised is the epistemology of civilization and how civilization is in the context of knowledge. This research uses a qualitative approach with a descriptive model that analyzes various articles through Google Scholar which is related to the epistemology of civilization itself. The analysis results showed that the epistemology of civilization in the changing world is a development of human culture and lifestyle as a transition from humans who live with instinct to humans who use more reason. As historical records, evidence, and discoveries related to changes in human life from time to time to modern times. The development of this research can be carried out by the case study method so as to strengthen the evidence of the Islamic practice itself.